This action might not be possible to undo. Are you sure you want to continue?

x

Deﬁne L(x) =

t=1 x

1 t 1

dt for x > 0. dt > 0 for x > 1. dt = 0. dt < 0 for x < 1. 1 t > 0.

L(x) = 1 t L(1) = L(x) =

t=1 t 1 1 t=1 x t=1

y=

t 1 t

L(x) is increasing, since

L(x) 0 1 x

t

y

x

L(x) = 1

y

1 t 1 t

dt for x > 0.

=

( x) L

t=1 1

L(1) =

t=1

dt = 0.

0

1

x L(x) > 0 for x > 1. L(x) < 0 for x < 1. L (x) = 1 x > 0. 1 x2 < 0.

L (x) = −

Since y = L(x) is an increasing and continuous function, it has an increasing and continuous inverse x = E(y). y = L(x) = L(E(y)) x = E(y) = E(L(x)) E is deﬁned for all real values of y. E takes on all positive real values of x. 1 x

) E (y x=

0 y

b

**It was shown earlier that the integral certain Riemann Sums, i.e., that
**

b a a

1 t

dt was a limit of

1 t

dt = lim

b a

1 n

n→∞

− 1 n, for any a > 0, b > 0,

which depends only on the ratio between a and b. With a = 1 and b = x, this means that the function L satisﬁes x1 1 n − 1), for any x > 0. dt = lim n(x L(x) = n→∞ 1 t We are about to see that its inverse function E is equal to E(y) = lim

n→∞

1+

y n

n

, for any y.

**Working from L(x) = lim n x − 1 ,
**

n→∞

1 n

y = L(x) = n x − 1 + o(1), as n → ∞, y + o(1) n y + o(1)

n

1 n

= x − 1, = x , = x = E(y).

1 n

1 n

1+ 1+

n y − o(1) n

**Now if y = u + o(1), this becomes 1+ u n
**

n

= E(u + o(1)) = E(u) + o(1). 1+ u n

n

Since E is continuous, we get E(u) = lim

n→∞

.

b a

1 t

dt = lim

b a

1 n

n→∞

− 1 n, for any a > 0, b > 0.

along with

x

L(x) =

1

1 t

**dt = lim n(x − 1), for any x > 0.
**

n→∞

1 n

give us

b a

1 t

b

dt = L 1 t

b a

b

b

and

a

1 t

dt = L(b) − L(a) b 1 −L a 1 .

since

a

dt =

1

1 t

a

dt −

1 t

dt = L

1

Since we have

b a

1 t

dt = L

b a

b

and

a

1 t

dt = L(b) − L(a),

= y, we can let a = x and b = xy, which makes = a x b = L(b) − L(a) so that L a becomes L(y) = L(xy) − L(x), and we get L(x) + L(y) = L(xy) for x > 0, y > 0.

b

xy

**For any positive a and b : L(ab) = L(a) + L(b) Second Proof:
**

ab

L(ab) =

t=1

1 t

a

dt =

t=1

1 t

ab

dt +

t=a

1 t 1

dt a du,

L(ab) = t a

L(a)

+

ab a

u= a a

au

where u =

, t = au, and dt = a du,

b

L(ab) = L(ab) =

L(a) L(a)

+

u=1

1 u

du,

+ L(b).

**For any positive a and b : L(ab) = L(a) + L(b) Third Proof: L(ab) − L(b) = lim n (ab) − 1
**

n→∞ n→∞ n→∞ n→∞ n→∞

1 n 1 n

− − −

1 n

n→∞

lim n(b − 1)) n(b − 1) b +1

1 n 1 n

1 n

**= lim n (ab) − 1 = lim n (ab) − 1 = lim n (ab) − b = lim n a − 1 b L(ab) − L(b) =
**

1 n 1 n 1 n 1 n

L(a) · 1

=

L(a).

**What does For any positive a and b : L(ab) = L(a) + L(b) mean for the inverse function x = E(y)? E(c + d) = E L E(c) + L E(d) =E L y=
**

L(a) + L(b) L(b) L(a) a b ab

, since y = L(E(y)),

E(c) · E(d) E(c) · E(d), since E(L(x)) = x. x

E(c) · E(d)

x

E(d) E(c)

x = E(y) y = L(x)

cd c+d

y

**For any c and d : E(c + d) = E(c) · E(d) Second Proof: E(c) · E(d) = lim
**

n→∞

1+ 1+

c n c n c

n

n

· lim 1+

n→∞

1+

n

d n

n

= lim = lim = lim = lim

d n d

n→∞

n

n→∞

1+ 1+ 1+ c

n + d

1+ +

n cd

n

n→∞

n n n2 c + d + o(1)

n

n = lim E(c + d + o(1)) = E(c + d).

n→∞ n→∞

Using L(x) + L(y) = L(xy) for x > 0, y > 0, we can get L x2 = L(x) + L(x) = 2L(x), L x3 = L x2 + L(x) = 2L(x) + L(x) = 3L(x), ··· L xp = L xp−1 + L(x) = pL(x), for any positive integer p, L xp = pL(x), for any integer p, positive or negative, since L xp + L x−p = L xp · x−p = L(1) = 0, L xp = −L x−p 1 1 L x q = L(x), for any nonzero integer q, 1 q 1 q = qL x q , since L(x) = L x q L x

p q

=L

x

1 q

p

= pL x

1 q

= p L(x) = L(x) q q

1

p

for any integer p, for any nonzero integer q, so we have L xk = kL(x) for x > 0, for rational k.

**L(xk ) = kL(x), for x > 0, for rational k. A Second Proof: Let k equal
**

k k

1 n

p q

. = lim n x − 1

n→∞

p nq

L(x ) = lim n (x ) − 1

n→∞

**Then restrict to n’s which are multiples of p : n = mp =
**

n=mp→∞

lim

mp x

p mpq

− 1 = p lim m x

m→∞

1 mq

−1 .

On the other hand, we also have p 1 lim r x r − 1 kL(x) = q r→∞ restricted to the r’s which are multiples of q : r = mq 1 1 p mq − 1 mq − 1 . lim mq x = p lim m x = m→∞ q r=mq→∞

L(xk ) = kL(x), for x > 0, for rational k.

A Third Proof: L(a ) =

t=1

1 k

k

ak

1 t

a

dt =

u=1

1 uk

k uk−1 du,

(where, if k = 0, u = t , t = uk , and dt = k uk−1du, ) a 1 k−1 u du, =k k u=1 u a 1 du, =k u=1 u = k L(a), and 1 1 dt = 0 = 0 L(a) and where, if k = 0, L(a0) = L(1) = t=1 t

**What does L(ak ) = kL(a) mean for the inverse function x = E(y)? E(kc) = E kL E(c) =E y =
**

kL(a) L(a) a ak

, since c = L(E(c)),

k k

L

E(c)

E(c) ,

since E(L(x)) = x. x

E(c)

k

x

E(c)

x = E(y) y = L(x)

c kc

y

**E(kc) = E(c) , for rational k A Second Proof: Let k equal E(kc) = lim 1+ p q kc again.
**

n

k

n→∞ n qn Then restrict to n’s which equal multiples mp of p : n = mp. pc mp c mp = lim 1 + = lim 1+ n=mp→∞ m→∞ qmp qm n→∞

= lim

1+

pc

n

while E(c)

k

=

r→∞

lim

1+

c r

r

p q

= lim

r→∞

1+

c r

rp q

**can be restricted to r’s which are multiples of q : r = qm, =
**

r=qm→∞

lim

1+

c qm

qmp q

= lim

m→∞

1+

c qm

mp

.

y=

4 5

1 t

3

L(3) =

t=1

1 t

dt

2 3

4 7

1 2 7 4

4 9 9 4

2 5 5 2

4 11 11 4

1 3

1

5 4

3 2

2 + 2 3

3 + 2 5 + 4

t + 1 3

L(3) > L(3) >

1 4 4 5

+

4 7

+

1 2

+

4 9

11

28271 27720

= 1.01987.. > 1

y= 1

4 5

1 t

L

5 2

=

5 2

1 t

dt

t=1

2 3

4 7

1 2 9 4

4 9 5 2 11 4

1

5 4

3 2

7 4

2 < 1 4

3 4 7 + 1 2 +

t 4 9

L

5 2 5 2

1+

4 5

+

2

5 2

+

L

<

2509 2520

= 0.996.. < 1

**Since L is a continuous function, and since L(2.5) is less than 1, and since L(3) is greater than 1,
**

L (x y=

)

y=1

the Intermediate Value Theorem implies that: there is at least one x between 2.5 and 3 where L(x) equals 1. (Since L is increasing, there can be no more than one such x.) There is exactly one e where L(e) equals 1. e = E(1) e = 2.71828182845904523536028747135266 24977572470936999595749669676277 24076630353547594571382178525166 4274274663919320030599218174136...

y

y=

1 t

Area = L(e) = 1 0 1 e t

y

1

L

L(e) = 1

x) (

e 0<x<∞ x

0

y

1

=

−∞ < y < ∞

Since L is continuous and increasing, it has a continuous and increasing inverse E. E is deﬁned for all real values of y. E takes on all positive real values of x. E(1) = e

y = E( x

)

x e

1

0

1

y

x e For rational k : k k since L x = kL(x) and E(ky) = E(y) , and since L(e) = 1 and E(1) = e, we have L ek = k and E(k) = ek .

1

ek x=

0

1

y

Positive integer powers were deﬁned in algebra as repeated products: xp = xx · · · x. Positive integer qth roots were deﬁned by taking the inverse function of the qth power function. (This was not usually possible without Greatest Lower Bounds and the Intermediate Value Theorem.) Fractional -th powers were deﬁned q p √ p as p-th powers of qth roots: x q = ( q x) or, equivalently, √ p q as qth roots of p-th powers: x q = xp. p

This is as far as deﬁnition of powers gets in algebra, √ without limits, without continuity. (No 3 2, 5π )

Since the function E is continuous as a real function, E is also continuous as a function on rational numbers: If lim (rational) kn = (rational) k, then lim ekn = lim E(kn) = E lim kn = E(k) = ek . n→∞ n→∞ n→∞ Powers of e are consistent under limits. We can extend the deﬁnition of “powers of e” using limits: If lim (rational) kn = (real) x, then we can deﬁne ex as ex = elim kn ≡ lim ekn = lim E(kn) = E lim kn = E(x) From now on, E(x) will be written as ex, even when no algebraic power or root is involved directly. E(c + d) = E(c) · E(d) will become ec+d = eced . E(ky) = E(y)

k n→∞

will become eky = (ey )k .

There is an inﬁnite, everywhere dense set of positive numbers x = ek , for which L(x) = L(ek ) = k = loge ek = loge x. Since L acts like a logarithm, and since L is continuous, we can extend the deﬁnition of log e for the other real numbers with ln x = loge x = L(x) as we just did for ex = E(x). From now on, L(x) will be written as ln x, the natural logarithm, even when no integer power of x equals any integer power of e. L(x) + L(y) = L(xy) will become ln x + ln y = ln xy . L(xk ) = kL(x) will become ln xk = k ln x .

y 1 y = ln x x

−3

−2

−1 −1 −2 −3

1 dy dx = 1 x

2

3

deﬁned for x > 0

y = ln (−x)

y 1 x

−3

−2

−1 −1 −2 −3 dy dx

1 = 1 −x

2 (−1) = 1 x

3

deﬁned for x < 0

y 1 y = ln |x| 1 −1 −2 −3 dy dx = 1 x 2 3 x

−3

−2

−1

on both sides

deﬁned for x = 0

d dx d dx d

ln f (x)

=

f (x) f (x) f (x) f (x) 1 · 1 = 1

with domain: f (x) > 0 with domain: f (x) = 0

ln |f (x)| = ln (ln x) =

with domain: ln x > 0, dx ln x x x ln x x>1 1 1 1 d ln | ln x| = · = with domain: ln x = 0 dx ln x x x ln x 0 < x < 1 and x > 1 1 d ln (ln |x|) = with domain: ln |x| > 0, dx x ln |x| x < −1 and x > 1 1 d ln | ln |x|| = with domain: ln |x| = 0, dx x ln |x| x = 0, x = ±1.

The function ln |f (x)| is deﬁned wherever f (x) = 0.

With the chain rule we also have: d ln |f (x)| = 1 f (x) f (x) = f (x) f (x) ,

dx f (x) f (x)

dx = ln |f (x)| + C,

but only on intervals where f (x) = 0.

d dx d dx d dx

ln f (x) ln |f (x)|

= =

f (x) f (x) f (x) f (x) 3 3x + 2

with domain: f (x) > 0 with domain: f (x) = 0 with domain: 3x + 2 > 0 x>− 2 3

ln (3x + 2) =

d dx

ln |3x + 2| =

3 3x + 2

with domain: 3x + 2 = 0 x=− 2 3

d dx =

ln

4

x6 + 1 1 4 · 6x5 x6 +1 = 3x5 2(x6 + 1) for all x

d 1 dx 4 d dx d dx

· ln (x6 + 1) = x−3

ln

x3 − 8 − ln |x3 − 8| − 3x2 x3 −8 for all x = 2, 3

=

ln |x − 3| = 1 x−3

d dx = d

ln

x3 − 8

x−3

dx

ln (x − 3) − ln (x3 − 8) = 1 x−3 − 3x2 x3 −8 if x > 3

=

d dx

ln (3 − x) − ln (8 − x3) = 1 x−3 − 3x2 x3 −8 if x < 2

3

To get area between x + y − 3 = 0 and xy = 2: Solve for intersections: (2,1) and (1,2) y

2

2

y =3−x y= 2 x

x=1

3−x−

2 x

dx

1

=

3 2

− 2 ln 2

0

0

1

2

x 3

f (x) f (x)

dx = =

1 f (x) 1 u

f (x) dx =

1 f (x)

d f (x)

du = ln u + C = ln |f (x)| + C 1 d(2x3 − 1) = ln |2x3 − 1| + C dx = 1 6 ln |2x3 − 1| + C

6x2 2x3 − 1 x2 2x3 − 1

dx = dx = 1 6

2x3 − 1 6x2

2x3 − 1

e4 1

1 x

dx = ln e4 = 4.

Substitution, using u = ln x, 1 x dx x(ln x)2

du dx

=

1 x

,

du =

1 x

dx =

dx x

f (ln x)

dx = = = −

f (u) du (ln x) 1 u

−2

dx x

= 1 ln x

u−2 du +C u du

2

+C = − dx

ln(x + a) x+a

dx = =

ln(x + a) u2 2

x+a 1 +C = ln(x + a) 2

=

+C

x y = ln x, dy dx d

y

x = ey ,

=

1

1 1 = = x = ey , e = = 1 dy dy dy x 1 dx d y e = ey , ey x= dy 0 d dx ex = ex , d2 dx ex = ex , 2 d3 dx ex = ex , 3

x dx

,

d x e = ex dx y 1 d4 dx ex = ex, .... 4

d dx d

ex = ex

**dx d 2x+1 3e = 3e2x+1(2) = 6e2x+1 dx d x x x1 e ln x = e ln x + e dx x d dx d dx e
**

√ x+1

ef (x) = ef (x)f (x)

=

e

√ x+1

√ 2 x

−x 2

3 − 2e

−x 3

= 3 3 − 2e = 6e

−x

· − 2e−x(−1)

3 − 2e

−x 2

eg(x)g (x) dx =

eg(x) d g(x) = eg(x) + C = eu du = eu + C (−2) dx = − 1 2 1 e−2x d − 2x

e

−2x

dx =

1 −2 1 2

e

−2x

xe

x2

dx =

= − e−2x + C 2 1 x2 x2 e (2x) dx = e d x2 2 1 x2 = e +C 2

d(cabin) cabin d

= log cabin,

d(mower) mower 1 x

= ln mower,

dx Hints: For For

(ln x) = 3(ln x) ·

3

2

for x > 0

e

−x

exdx , substitute u = ex + 1. √ x e +1

−1

2

dx, multiply out ﬁrst.

What happens when f is proportional to f ? An Important Equivalence: f (x) = Cekx if, and only if, f (x) = kf (x), and f (0) = C.

Proof of the “only if” part: If f (x) = Cekx, then f (0) = Cek·0 = Ce0 = C · 1 = C, and f (x) = Cekxk = kf (x).

An Important Equivalence: f (x) = Cekx if, and only if, f (x) = kf (x), and f (0) = C.

Proof of the “if” part: If f (x) = kf (x), then d dx f (x)e−kx = f (x)e−kx − f (x)e−kx(−k) = f (x) − kf (x) e−kx = 0,

so that f (x)e−kx is a constant, Therefore, we have f (x) = Cekx.

which equals f (0)e−k·0 = Ce0 = C.

Question: Would this have been a proof ? Since f (x) = kf (x), f (x) = k, then f (x) ln f (x) = kx + D = kx + ln C, f (x) = ekx+D = eD ekx f (x) = Cekx. Answer: This would not be legitimate unless you were already sure that f (x) and C were both positive.

An Application of f (x) = k · f (x) ⇔ f (x) = f (0)ekx: At the end of this course, a certain student knows about 90 percent of the subject. Consider f (0) to be 90. Assuming that he doesn’t use this knowledge, he will forget facts and skills at a rate of one ﬁfth per year of what he still remembers. Set k equal to −0.20. After t years, he still remembers 90e−0.20t percent of this course. After 2 years, he still remembers 90e−0.20·2 = 90e−0.4 = 60 percent of this course. After 4 years, he still remembers 90e−0.20·4 = 90e−0.8 = 40 percent of this course. USE IT OR LOSE IT!!

Combining u = ln v with v = eu, we can have v = eln v . Using this, for any rational number , the power xp/q q √ √ p p/q = ( q x) or as q xp. can deﬁned in algebra either as x ln xp/q p ln x p

= eq , Since this can also be written as xp/q = e if x is positive, we can take advantage of the continuity of the logarithm and the exponential functions to deﬁne an r-th power, for any real number r, whether r is rational or irrational, with xr = er ln x if x > 0.

For any positive a and any real b and c , (ab)c = abc. Proof: Apply xz = ez ln x to c b c = eln ab = ec ln ab = ec(b ln a) = e(cb) ln a = abc. a For any positive a and any real b and c, ab + c = ab · ac. Proof: Apply xz = ez ln x to ab + c = e(b + c) ln a = eb ln a + c ln a = eb ln a · ec ln a = ab · ac

Diﬀerentiating xr = er ln x, d

if x is positive, we have

r = d er ln x = er ln x d (r ln x) = er ln xr 1 x dx dx dx x = er ln x re− ln x = re(r − 1) ln x = rx(r − 1), the usual rule for the derivative of a constant power. The antiderivative rule still works here, also. Examples: d dx x

√ 2

xπ = πxπ−1

√ 2+1

x +C dx = √ 2+1

On the other hand, if we raise a positive constant p to a power we will have d x ln p d x x ln p d (x ln p) = px(1 ln p). p = e =e dx dx dx d x p = px ln p dx Examples: d dx d 2x = 2x ln 2 3x = 3x ln 3

dx d 10x = 10x ln 10 dx d x e = ex ln e = ex dx

If we combine this with the chain rule, we can have d f (x) p = pf (x) ln p f (x). dx Examples: d x3 2 = dx d x2 3 = dx d x3 ln 2 3x2 2 x2 ln 3 2x 3

dx d f (x) e = ef (x)f (x). dx

10sin x = 10sin x ln 10 cos x

Powers Deﬁned by the Natural Logarithm and Exponential: If x is positive, x equals eln x and xz equals ez ln x. This was motivated by the fact for rational k that xk = eln x For a constant real a, we have d dx x =

a k

= ek ln x.

d

**dx dx x = aea ln xe− ln x = ae(a−1) ln x = axa−1. d x
**

√ 2

e

a ln x

=e

a ln x

d

(a ln x) = e

a ln x a

Examples:

dx x

√ 2

=

√

2x

√ 2−1

,

d dx

xπ = πxπ−1, xπ+1 π+1 + C.

x + C, dx = √ 2+1

√ 2+1

xπ dx =

**For a constant positive real b, we also have: d dx d2 dx b =
**

x

d dx

e

x ln b

=e

x ln b

d dx

(x ln b) = ex ln b(ln b) = bx(ln b),

bx = bx(ln b)2, 2 ex ln bdx = d dx

x

d3

bxdx = Examples:

dx ex ln b ln b

x

bx = bx(ln b)3, 3 +C = bx ln b d dx + C. π x = π x(ln π), πx ln π + C.

10 = 10 (ln 10), 10x ln 10 + C,

10xdx =

π xdx =

To diﬀerentiate u(x)v(x) : d v(x) ln u(x) d v(x) v(x) ln u(x) d u(x) e (v(x) ln u(x)) = =e dx dx dx u (x) v(x) ln u(x) v (x) ln u(x) + v(x) =e u(x) u (x) v(x) v (x) ln u(x) + v(x) = u(x) u(x) d dx u(x)v(x) = u(x)v(x) ln u(x) · v (x) d dx + v(x)u(x)v(x)−1 · u (x), if u(x) > 0. uv = uv ln u · v + vuv−1 · u , if u > 0.

Logarithmic Diﬀerentiation: y(x) = u(x)v(x) ln y(x) = v(x) ln u(x) y (x) u (x) = v (x) ln u(x) + v(x) y(x) u(x) y (x) = y(x) v (x) ln u(x) + v(x) y (x) = u(x)v(x) u (x) u(x) u (x) v (x) ln u(x) + v(x) u(x)

d dx

u(x)v(x) = u(x)v(x) ln u(x) · v (x) + v(x)u(x)v(x)−1 · u (x), if u(x) > 0.

To Diﬀerentiate xx : d x ln x d x x = e dx dx x ln x d (x ln x) =e dx 1 x ln x ln x + x =e x = xx ln x + 1

Logarithmic Diﬀerentiation: y = xx ln y = x ln x y y x y = y ln x + 1 y = xx ln x + 1 xx = xx ln x + 1 = ln x + x 1

A Rule of Thumb for Derivatives: If x appears more than once in the formula for f (x), label the appearances of x as x1, x2, x3, ...xn. Call this function F (x1, x2, x3, ...xn), temporarily. Diﬀerentiate F partially with respect to each xk . Add up the partial derivatives, with each xk written again as x.

Example: f (x) = g(x) + h(x) F (x1, x2) = ∂F = ∂x1 ∂F = ∂x2 Add: f (x) = g(x1) + h(x2)

Example: f (x) = g(x) − h(x) g (x1) −h (x2) g (x) − h (x) g(x1) − h(x2)

F (x1, x2) = ∂f g (x1) = ∂x1 ∂f h (x2) = ∂x2 g (x) + h (x) Add: f (x) =

Example: f (x) = g(x) · h(x) F (x1, x2) = ∂F = ∂x1 ∂F = ∂x2 Add: f (x) =

g(x1) · h(x2) g (x1) · h(x2) g(x1) · h (x2)

g (x) · h(x) + g(x) · h (x)

Example: f (x) = F (x1, x2) = ∂F ∂x1 ∂F =

g(x) h(x) g(x1) h(x2) g (x1)

h(x2) g(x1) h (x2) =− 2 ∂x2 h (x2) g(x) g (x) − 2 h (x) Add: f (x) = h(x) h (x) g (x)h(x) − g(x)h (x) f (x) = h2(x)

Example: f (x) = u(x)v(x) F (x , x ) = u(x )v(x2)

1 2 1

∂F ∂x1 ∂F

= v(x2)u(x1)v(x2) − 1u (x1) = u(x1)v(x2) ln u(x1)v (x2)

∂x2 Add: f (x) = v(x)u(x)v(x) − 1u (x) + u(x)v(x) ln u(x)v (x) d dx u(x)v(x) = u(x)v(x) ln u(x) · v (x) d dx

uv = uv ln u · v + vuv − 1 · u ,

+ v(x)u(x)v(x) − 1 · u (x), if u(x) > 0. if u > 0.

v(x)

Example: f (x) =

t=u(x) v(x1)

g(x, t) dt g(x3, t) dt

t=u(x2)

F (x1, x2, x3) = ∂F ∂x1 ∂F ∂x2 ∂F

= g(x3, v(x1))v (x1) = −g(x3, u(x2))u (x2)

v(x1)

∂x3 ∂x3 t=u(x2) Add: f (x) = g(x, v(x))v (x) − g(x, u(x))u (x) v(x) ∂g(x, t) dt + ∂x t=u(x)

=

∂g(x3, t)

dt

A Limit as a Byproduct of the Derivative lim

d

h→0

dx ln (x + h) − ln x h x+h x

1 h

ln x = = =

1 x 1 x 1 x

:

h→0

lim ln 1 +

h x

1 h

= lim ln

h→0

At x = ln

1 a

:

1 h 1 h

h→0

lim 1 + ha

n

= lim ln 1 + ha

h→0

1 h

= a

n→±∞

lim ln 1 +

a n

= lim 1 + ha

h→0

= ea

Another Limit as a Byproduct of a Derivative: For b > 0: d lim dx bx+h − bx h bx = bx ln b : = bx ln b

h→0

At x = 0:

h→0

lim

bh − 1 h

= ln b

n→±∞

lim n b − 1

1 n

= lim

h→0

bh − 1 h

= ln b

On Logarithms in General Consider any function f which,like the natural logarithm L, satisﬁes f (xy) = f (x) + f (y) for all x and y in its domain: If f were deﬁned at x = 0, then we would have f (0) = f (x · 0) = f (x) + f (0), which would require f (x) to equal zero for all x in its domain. The only such function f would be the constant zero –not very interesting.

Now consider any function f satisfying f (xy) = f (x) + f (y) and which is deﬁned only for x > 0 and y > 0: If x = y = 1, then f (1) = f (1) + f (1), giving f (1) = 0. Also, for a ﬁxed x > 0, is equivalent to f (x + h) = f (x) + f (x)h + o(h) h x h = f (x) + f (x)h + o(h) = f (x) + f (x)x h +o h

f x 1+

is equivalent to f (x) + f 1 + is equivalent to

x x x f (1 + k) = f (1) + f (x)xk + o(k)

If the function f is diﬀerentiable at any x > 0, then it is diﬀerentiable at x = 1, and f (1) = f (x)x.

Alternatively: Consider any function f which satisﬁes f (xy) = f (x) + f (y) for all x > 0 and y > 0: If x = y = 1, then f (1) = f (1) + f (1), and f (1) equals 0. If f is diﬀerentiable at any positive x, then f (x) = lim f (x + h) − f (x) h f (x) + f 1 + = lim

h→0 h x

f x 1+ = lim − f (x) f 1+

h x h x h→0

h x

− f (x)

h→0

h

h f 1+

h x

= lim

−0

h→0

h 1 x

= lim

− f (1))

h →0 x

·

1 x

f (x) = f (1) ·

, and f is diﬀerentiable at all positive x.

So far, f (xy) = f (x) + f (y) for all x > 0 and y > 0:

**would imply that f (1) = 0 and that f (x) = f (1) · x if f is diﬀerentiable for any, and thus all, positive x. f (x) = f (x) − 0 = f (x) − f (1) =
**

x x

1

f (t)

x 1

=

1

f (t) dt =

x 1

= f (1) ·

1 t

1

f (1) ·

1 t

dt

dt = f (1) · ln(x).

Any function f satisfying f (xy) = f (x)+f (y), for x, y > 0, and which is diﬀerentiable at some x0 is diﬀerentiable for all other x and equals a constant times the natural logarithm: f (x) = C ln(x).

Now consider the following constant multiple of ln x: ln(x) 1 ln(x) = f (x) = ln(10) ln(10) For any rational k we have k ln(10) ln(10k ) k f (10 ) = = = k = log10 (10k ) ln(10) ln(10) (In algebra log10(x) was deﬁned only for rational powers of 10.) Now, deﬁne log10(x) to be this ln(x) ,

ln(10) for all positive real x, not just for powers of roots of 10. Similarly, for any positive b = 1, deﬁne log b(x) to be This agrees with loge(x) = ln(x) ln(e) = ln(x) 1 = ln(x). ln(x) ln(b) .

For any x > 0, b > 0, with b = 1, logb x =

ln x ln b

.

A very handy rule for working with diﬀerent bases: For any a, b, c > 0, with b, c = 1, ln a Proof: ln a = ln c ln b ln b ln c logb a = logc a logc b

**4 log2 16 = , Examples: log8 16 = log2 8 3 log1000 100
**

−4 5

=

log10 100

−4 5

log10 1000

=

− 4 log10 100 5 log10 1000

=−

8 15

.

Some Important Powers: 21 = 2 22 = 4 23 = 8 24 = 16 25 = 32 26 = 64 27 = 128 28 = 256 29 = 512 210 = 1024 211 = 2048 212 = 4096 31 = 3 32 = 9 33 = 27 34 = 81 35 = 243 36 = 729 37 = 2187 38 = 6561 39 = 19683 310 = 59049 311 = 177047 312 = 5314412 51 = 5 52 = 25 53 = 125 54 = 625 55 = 3125 56 = 15625 57 = 78125 58 = 390625 59 = 1953125 510 = 9765625 511 = 48828125 512 = 244140625

Example: f (x) = x log5 x = (x ln x) ln 5

x ln x ln 5

=

1 ln 5 1

x ln x

1 ln x + x = ln 5

f (x) =

x = ln x + 1 ln 5

(It is not necessary to use the entire quotient derivative formula, here.) ln (log5 x) ln = ln x

Example: f (x) = log3 (log5 x) = ln 3 ln ln x − ln ln 5 = ln 3 1 −0 1 x ln x = f (x) = ln 3 x ln x ln 3

ln 5 ln 3

Formulas to Remember y = ln x; 1 = ln e; ln ab = ln a + ln b ln y k = k ln y, y = ln ey , logb a = logc a logc b ey = x; e1 = e; ec · ed = ec+d; ec k = ec·k eln x = x; ab = eb·ln a;

- Graphics Slides 14
- Graphics Slides 13
- Graphics Slides 12
- Graphics Slides 11
- Graphics Slides 08
- Graphics Slides 07
- Graphics Slides 06
- Graphics Slides 05
- Graphics Slides 04
- Graphics Slides 03
- Graphics Slides 02
- Graphics Slides 01
- 87 Cotangent BernoulliRevisited
- 86-PowerSeriesOperations
- 85-PowerSeries
- 85-InfiniteIntervalIntegral
- 84-AbsoluteandConditionalConvergence
- 60-IntegrationByParts
- 61-IntegratingTrigPowers
- 59 L'Hospital
- 57-Trigintegral
- 58 Hyperbolic
- 56-InverseTrig
- 54-IntegralSubstitution

Sign up to vote on this title

UsefulNot useful- Funcion Gamma
- _Domain and Range).pdf
- 06 Lecture 1
- Ειδικές Συναρτήσεις
- Curve Sketching
- 100-2-Limits
- Chapter 4 Quiz
- Functions
- CK-12-PreCalculus-Concepts b v509 Pe8 s1
- A new additive function and the F. Smarandache function
- Notes
- Complcex Fun Branch Theory
- Square and Square Roots
- Partial Permutation
- Inverse Functions
- team-solutions.pdf
- Math_book Surd, Indices and Log
- Math Formulas 1.0
- Binomial- With R
- Functions
- Limits at a Point
- 04 Cetking Functions Basics
- Fundamental Engineering Maths 1
- Inverse Functions
- 1 995 Mathematics Olympiad Lecture Notes - Review of Logarithms - Greg Gamble - Logs
- Chapter 1 calculus 1
- Finding the Inverse of a Function
- lec21
- Weatherby_JNT-2011
- 1 1 Inverse
- 55-LogarithmExponential

Are you sure?

This action might not be possible to undo. Are you sure you want to continue?

We've moved you to where you read on your other device.

Get the full title to continue

Get the full title to continue reading from where you left off, or restart the preview.

scribd